Prevalence of postpartum depression in mothers of infants with cleft lip and/or palate and its influential factors: a mixed-methods study - Shuai Yang; Jiansuo Hao; Xiaofang Liu; Yunxia Lv; Huaitian Xue; Mengjie Wang; Min Zhu (BMC Pregnancy and Childbirth)
Abstract Background Mothers of infants with cleft lip and/or palate (CL/P) are at an elevated risk of postpartum depression due to emotional challenges associated with the condition. This study aimed to examine the prevalence of depression and its influential factors in mothers of infants with CL/P within 1 year postpartum. Methods This study used an interpretive sequential mixed research design, incorporating the psychological-social-cultural model to understand the phenomenon under investigation. A quantitative survey was conducted from February to August 2023, involving 254 mothers of infants with CL/P from two hospitals in China, to investigate the prevalence of depression within 1 year postpartum and its influential factors. Subsequently, qualitative interviews were performed to gain insights into how these factors affect postpartum depression within this specific population. Results The prevalence of depression among mothers of infants with CL/P was 23.6% within 1 year postpartum, peaking at 33.3% between 4 and 6 months postpartum. Multivariate logistic regression analysis indicated that mothers of infants with CL/P with a history of adverse pregnancies are more likely to experience depression (odds ratio (OR) = 5.713, p<0.001). Mothers without postpartum caregiving support were significantly more likely to experience postpartum depression (OR = 1, p = 0.004) compared to those who received care from family members (OR = 1.219) or nannies (OR = 1.166). Increased parenting stress was also associated with a higher likelihood of depression (OR = 1.267, p < 0.001). In contrast, mothers with greater social support were less likely to develop postpartum depression (OR = 0.970, p = 0.041). Cultural factors also play a role in shaping postpartum depression among mothers of infants with CL/P. This relationship is complex, involving both adherence to traditional customs and the conflicts that arise between these customs and modern health practices. Conclusion Postpartum depression is more prevalent among mothers of infants with CL/P compared to mothers of infants without CL/P. Mothers with adverse pregnancy history, lack of caregiver support, and increased parenting stress were found to have a greater risk of postpartum depression. Conversely, higher levels of social support were associated with a reduced likelihood of experiencing postpartum depression. The influences of cultural factors on postpartum depression are complex, and they also shape an individual’s social support in multiple ways. Regular prenatal evaluations are recommended to mitigate psychological burdens. Furthermore, family members should provide comprehensive support, and social groups are encouraged to arrange multifaceted assistance to families facing the challenges of caring for infants with CL/P.